KYNURENIC ACID A TRYPTOPHAN METABOLITE INDUCES BONE LOSS IN MICE. (11th November 2018) - Isales, C; Ding, K; Bollag, W; McGee-Lawrence, M; Hill, W; Shi, X; Elsalanty, M; Hamrick, M
Abstract: The generation of reactive oxygen species increases with age and may play a pathogenic role in the development of osteoporosis. We previously reported that kynurenine (kyn), the initial metabolite in tryptophan oxidation, accumulates with age and feeding kyn to younger mice results in an accelerated aging bone phenotype. Kyn has also been linked to neurodegenerative disorders such as Alzheimer's disease. Kynurenic acid (KNA) is a further downstream product of tryptophan oxidation but, in contrast to kynurenine, has been reported to be neuroprotective by blocking the NMDA receptor. Thus, we hypothesized that KNA might also be osteoprotective. To test this hypothesis, in an IACUC-approved protocol, we fed KNA to aged (22-month-old) C57BL/6 mice for eight weeks. The mice were divided into three groups: Control (Con), +Low Dose KNA (37.5 ppm, LoKNA); +High Dose KNA (375 ppm, HiKNA). The mice were then sacrificed and bones collected for analysis. KNA feeding had no impact on mouse weight (36.0 ± 3.6, 36.1 ± 3.6, 35.8 ± 3.8gm, means±SD, n=10/group). However, increasing KNA concentration resulted in bone loss as measured by DXA: femoral bone mineral density (BMD): 0.057 ± 0.0026 vs 0.057 ± 0.0021 vs 0.053 ± 0.0037, Con vs LoKNA vs HiKNA (means±SD; p<0.05 Con vs HiKNA). Similarly, microCT showed a decrease in bone volume/total volume (BV/TV%) in the HiKNA group: 15.78 ± 1.37 vs 17.76 ± 2.88 vs 14.79 ± 1.27, Con vs LoKNA vs HiKNA; means±SD). High-dose KNA also decreased trabecular number and thickness as measured by microCT. These data suggest that in contrast to potential neuroprotective effects in the brain, KNA promotes bone loss in the periphery.